Color tunability and energy transfer studies of Dy3+/ Eu3+ co-doped calcium aluminozincate phosphor for lighting applications. (August 2019) - Kaur, Sumandeep; Rao, A.S.; Jayasimhadri, M.
Graphical abstract: Partial energy level diagram representing energy level of Dy 3+ and Eu 3+ ions and transitions observed in calcium aluminozincate phosphor. Highlights: Dy 3+ /Eu 3+ co-doped CAZ phosphors were synthesized by using Pechini sol-gel method. The as synthesized phosphors show intense white emission under 363 nm excitation. The energy transfer between Dy 3+ and Eu 3+ ions is via dipole-dipole interaction. The thermoluminescence study reveals presence of shallow and deep trap centres. Abstract: Dy 3+ doped and Dy 3+ /Eu 3+ co-doped calcium aluminozincate (CAZ) phosphor synthesized by Pechini sol-gel method. Structural and morphological analysis were carried out by using X-ray diffractometer (XRD) and field emission scanning electron microscope (FE-SEM). The photoluminescent (PL) spectra were recorded and energy transfer mechanism between Dy 3+ and Eu 3+ ions were studied using Dexter and Reisfeld's approximation. The colorimetric properties were studied by evaluating CIE coordinates and correlated color temperature (CCT). The energy transfer mechanism was analysed by applying Inokuti-Hirayama (I-H) model on decay curves as well. The thermoluminescence (TL) glow curve analysis reveals two trap centres in the present host. The obtained results indicate that the CCT can be tuned from warm to cool region and color tunability can also be achieved in Dy 3+ /Eu 3+ co-activated CAZ phosphor by varying the excitation wavelength or activator concentration in the host lattice and hence can be effectively utilized in white light emitting diodes (wLEDs).